P131 Pleural nurse specialists: an evolving role within the national health service. (11th November 2022) - Li, D; Johnstone, S; Hinchcliffe, F; Vella, C; Sudhir, R; Panchal, R
Abstract : The Getting It Right First Time (GIRFT) Programme published its national report in September 2021 and highlighted pleural disease as a common condition affecting patients in the National Health Service (NHS). It highlighted the need to reduce hospitalisations and provide a high-quality service. Dedicated nurses to facilitate procedures and provide specialist patient care are required. Our aim was to create a survey to understand the role of the pleural nurse specialist in centres nationwide. A survey was sent to pleural nurse specialists via the UK Pleural Society. Information was gathered regarding banding, procedural competencies, and nurse-led clinics. Feedback was sought regarding the role including its potential future directions. 29 responses were received. 48.3% responders were band 7 nurses, with the minority being band 6 and 8 nurses, advanced care practitioners and 1 nurse consultant. Most nurses were competent to perform ward tasks including talc slurry pleurodesis. Over 2/3 of responders were competent in thoracic ultrasound however only 55% and 52% were able to perform diagnostic and therapeutic aspirations. 45% and 34% were able to insert chest drain or indwelling pleural catheter (IPC). One nurse consultant was competent to perform thoracoscopy. 69% nurses lead specialist nurse-led pleural clinics. This survey highlights the differences in nurse specialists across the centres, including the disparity in procedural competences. There is vast potential for the role of pleural nurse specialists, and therefore, it is vital that further training and resources are provided.